“VULNERACIÓN DEL DERECHO AL DEBIDO PROCESO POR CONDENAS A COSTAS PROCESALES INMOTIVADAS EN JUICIOS EJECUTIVOS EN ECUADOR” - Uyaguari Vega, Scarleth Eloísa (2024)
This Curricular Integration Work is entitled: “Infringement of the Right to due process by sentences to unmotivated procedural costs in executive trials in Ecuador”, and the interest arises to develop this thematic because currently there is a violation of the Right to due process to the procedural actors in executive trials, where at the time of establishing the procedural costs the judge omits the Constitutional Right of motivation in the sentences, leaving the defendant defenseless, forcing him to file appeals, or in special cases, reaching to file extraordinary actions of protection, before the Constitutional Court. Despite the existence of Constitutional and Judicial Function regulations that oblige the judges of the National Courts and Judicial Units to motivate their sentences in order to guarantee the right to defense of the procedural parties, as well as the right to legal certainty in judicial proceedings. Thus, every judicial decision must be motivated, and according to the evidence provided in the trial and other evidentiary documents, the injured right must be reestablished, without violating other rights, however, the judges in civil matters within the executive trials, in the consideration part of the sentence do not motivate their decision to determine the procedural costs that must be paid by the sentenced parties; This generates non-observance of the due process, in particular the right of motivation, since the judge must argue that within the process the malicious conduct of the defendant, procedural disloyalty or abuse of law has been proven. In the development of the present work of Curricular Integration, materials and methods were used, which were mentioned within the project of the work, indicating in this the elaboration of surveys and interviews to Law Professionals of the city of Loja, who provided useful and relevant information for the development of this research work, so that, upon reaching the conclusion I have considered the need to raise propositional guidelines as results of the analysis and interpretation of the sentences of the Constitutional Court where the violation of the Right to the motivation of the sanction to procedural costs in first level sentence is evidenced; which obliges the affected party to file appeals, even to the point of filing an extraordinary action for protection.